Determination Of Total Flavonoids Extract of White (Magnolia Alba (Dc.) Figlar) Using Spectrophotometry UV-Vis Method - Mastura, Mastura; Amna, Ulil; Niaci, Sarah; Pebiola, Tia (Journal of Carbazon, 2024)
Flavonoids are a group of secondary metabolites produced by plants that have the potential to influence pharmacological activity. This study aims to determine the total flavonoid content of the ethanol crude extract of white cempaka flowers (Magnollia alba(DC.) Figlar) using the UV-Vis spectrophotometry method. This study used colorimetric and spectrophotometric methods using quercetin as a comparison. The qualitative test research results proved that cempaka putih (Magnolia alba(DC.) Figlar) flowers contain flavonoid coumpound. Then a maximum wavelength of 432 nm is obtained with an absorbance of 0.1236, the absorbance calculation for each quercetin concentration and the sample is calculated using a maximum wavelength of 432 nm. Based on the linear regression equation obtained from the standard quercetin curve, the total flavonoid content of the crude ethanol extract of cempaka putih flowers with 3 different concentration variations, at a concentration of 100 ppm, the results obtained for the total flavonoid content were 276,83 17,7 mgQE/g, 500 ppm. total flavonoid levels of 105,189 8,16 mgQE/g, 1000 ppm obtained total flavonoid levels of 79,115 8,33 mgQE/g.